Dinamika Hukum Pemilihan Kepala Daerah Serentak Tahun 2024 - Darmawan, Darmawan; Falah, M. Fajrul (Fakultas Syariah INSURI Ponorogo, 2022)
Regional head elections are one form of democracy implementation in Indonesia. Regional head elections are carried out directly on the principles of being free, honest and democratically fair. After the enactment of Law Number 1 of 2015 which was last amended by Law Number 6 of 2020 concerning the election of governors, regents and Mayors, the regional head elections will be held simultaneously in 2024. This implementation will have the potential to cause problems, resulting in many regional governments without a head. The definitive area and will be led by the regional head officer. In addition, there will be regional heads whose terms of office have been shortened. The author will examine these problems using normative legal research, using a statue approach and a historical approach, to find out the legal implications of simultaneous regional head elections and the effectiveness of their implementation. Based on this research, it was found that there is a need for revitalization of regulations regarding filling the positions of regional heads during this transition period, by giving provincial legislatives council the authority to elect and appoint regional head officials, or conduct simultaneous regional head elections nationally in 2027 in order to run effectively and efficiently